Diabetes Assistant: A Blood Sugar Monitoring and Management System - EMRI, NURUL AMIRAH; MAT REJAB, MAZIDAH (Applied Information Technology And Computer Science, 2025)
Diabetes is a chronic disease affecting millions globally, dependent on rigid management of blood sugar, diet, and medication. Al-Fatah Clinic, rely on paper records, which bring about many errors, inefficiencies, and incompleteness in tracking. Many patients face problems in managing their dietary needs and routine health checks, thus affecting their outcomes poorly. The Diabetes Assistant System brings a mobile-view web paltform for patients and web-based platform for clinicians.  This includes blood glucose recording, reminder notification, medical feedback from doctor and generate report. Clinicians are benefited by remote monitoring dashboards and patients management and also patient report  through this system for personalized healthcare. It was build using the Waterfall model and perform alpha and beta testing to ensure system reliability.  This system targets patients and clinician for diabetes management with a view to digitizing record-keeping at Al-Fatah Clinic and ensuring quality care. It empowers users within one ecosystem by increasing adherence and quality long-term health outcomes.